PENGEMBANGAN INOVASI KURIKULUM BAI BERBASIS NILAI-NILAI AL ISLAM DAN KEMUHAMMADIYAHAN DI SEKOLAH MUHAMMADIYAH - Asmira Efendi; Ihsan Muhadi (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
This study aims to examine the development of curriculum innovation for Islamic Religious Guidance (BAI) in Muhammadiyah schools in Karanganyar, using a values-based approach grounded in Al-Islam and Kemuhammadiyahan (AIK). Muhammadiyah schools play a strategic role in shaping students' character to be religious, progressive, and morally upright. However, the BAI curriculum still faces challenges in terms of relevance and contextualization of AIK values in the modern era. This research employs a qualitative descriptive approach with data collected through observation, interviews, and document analysis at several Muhammadiyah schools in Karanganyar. The findings reveal that some schools have introduced innovations by integrating AIK values into thematic learning, implementing character-based tahfiz programs, encouraging daily worship habits, and utilizing digital media for student da’wah. Core AIK values—such as monotheism (tauhid), ethics (akhlak), enjoining good and forbidding wrong (amar ma’ruf nahi munkar), and renewal (tajdid)—are embedded not only in instructional materials but also in the school's culture. Nonetheless, challenges remain, including limited human resources of innovative AIK teachers, lack of curriculum development training, and minimal synergy between schools and the Muhammadiyah Education Council. The article recommends strengthening AIK teacher training, developing a contextual curriculum model based on local Karanganyar wisdom, and fostering active collaboration between schools and Muhammadiyah organizational structures to support the transformation toward progressive Islamic education.